The Lexical Interference of Islamic Missionary Utterance in Pekalongan (Universitas Negeri Semarang, 2018)
Islamic missionary inclined into another languages when speaking Indonesian. This situation is to cause indifferenced principle of the language and resulting in a interference. Lexical interference greatly affect to Islamic missionary utterance in Pekalongan. The purpose of this research was to describe lexical interference Islamic missionary utterance in Pekalongan. The data were collected by observation method and continued by using the technique of uninvolved conversation observation, recording, and noting. Furthermore, the data were analyzed using comparative method and determinant-sorting technique. Interference is a deviation from one language rule into another language rule. Interference in the utterance of Islamic missionary occurs because speakers use Javanese, Arabic, and English in the structure and rules of the Indonesian. Lexical interference inclined by Islamic missionary in Pekalongan, Central Java, Indonesia. The use of lexicons is prone to interference, including nouns, pronouns, verbs, and adjectives.